A novel approach to L1 filter design for asynchronously switched positive linear systems with dwell time. (14th August 2019) - Li, Yang; Du, Wenju; Xu, Xiaozeng; Zhang, Hongbin; Xia, Jianwei
Summary: In this paper, the L 1 filtering problem is studied for continuous‐time switched positive linear systems (SPLSs) with a small delay existing in the switching of the filter and the subsystem. Unlike the existing literature concerned with asynchronous problems of SPLSs, the synchronous and asynchronous filters will be designed separately, which implies less conservative results. By introducing a class of clock‐dependent Lyapunov function (CDLF), which jumps down when the modes of the filter or the subsystem change and may increase or decrease during the asynchronous interval, clock‐dependent sufficient conditions characterizing a nonweighted L 1 ‐gain performance of the filter error systems are established. Then, based on the L 1 analysis results, a pair of error‐bounding filters are designed to estimate the outputs of SPLSs. The filter gains can be obtained by solving a set of linear programming. Finally, two numerical examples are presented to show the effectiveness and advantages of the results.